Guidelines for single fiber EMG. Issue 8 (August 2019) - Sanders, Donald B.; Arimura, Kimiyoshi; Cui, LiYing; Ertaş, Mustafa; Farrugia, Maria Elena; Gilchrist, James; Kouyoumdjian, João Aris; Padua, Luca; Pitt, Matthew; Stålberg, Erik
Highlights: This paper is an IFCN-endorsed Guideline written by international experts. It reviews the current status of single fiber EMG (SFEMG) and the measurement of jitter with concentric needle electrodes. It presents pitfalls of measuring jitter with single fiber and concentric needle electrodes. Abstract: This document is the consensus of international experts on the current status of Single Fiber EMG (SFEMG) and the measurement of neuromuscular jitter with concentric needle electrodes (CNE – CN-jitter). The panel of authors was chosen based on their particular interests and previous publications within a specific area of SFEMG or CN-jitter. Each member of the panel was asked to submit a section on their particular area of interest and these submissions were circulated among the panel members for edits and comments. This process continued until a consensus was reached. Donald Sanders and Erik Stålberg then edited the final document.